Loneliness is not associated with attention interference of negative social information: Evidence from four studies - Anita Restrepo; Emily M. Silver; Karen E. Smith; Sabina Raja; Frederica Rockwood; Colleen Wohlrab; Kelly E. Faig; Greg J. Norman (PLoS ONE, 2025)
Extended experiences of loneliness, defined as perceived social isolation, are associated with lasting impacts on health outcomes. One proposed mechanism through which loneliness contributes to health risk is heightened vigilance to cues of social threat resulting in extended activation of stress responses systems. This heightened vigilance is thought to be driven by loneliness-related shifts in a variety of cognitive and affective processes, though the differential effects of loneliness on specific stages of processing remain unclear. The present study examined four datasets using individual participant data meta-analytical techniques to test the link between loneliness and attention interference to social threat cues in an Emotional Stroop task. Despite existing theoretical frameworks predicting heightened attentional interference for negative social information in lonely individuals, we found no support for this effect across the four samples. These findings highlight the need for further work delving into the complex interplay between distinct perceptual processes associated with loneliness and how they contribute to the maintenance of loneliness states over time.